Ethanol extract of soursop leaf inhibits acid production and adhesion of Streptococcus mutans - Rahman, Friska Ani; Intan, Rahsunji (Padjadjaran Journal of Dentistry, 2021)
Introduction: Dental caries and dental plaque are the most popular global oral health problems. The primary step of dental caries is characterized by damage of tooth surfaces  affected by acids which are by-products of sugar metabolism by a cariogenic bacteria. One of the cariogenic bacteria is Streptococcus mutans. Annona muricata is traditionally applied as an herbal remedy for various illnesses and has been recognized in a previous study as an antimicrobial agent. This study was aimed to determine  inhibition of ethanol extract of soursop  on acid production and adhesion of Streptococcus mutans. Methods: Soursop leaf extracted by maceration using 70% ethanol solvent. The extracts obtained were tested at various concentrations. To examine the effect of ethanol extract of Soursop on acid production by S. mutans, the pH of the culture was determined using a pH meter. Inhibition of adhesion of S. mutans to the saliva-coated hydroxyapatite (S-HA) discs was quantified using colony counting on TYS20B agar plates. Results: Ethanol extract of soursop showed  significant inhibition of acid production at the concentrations of 50, 75, 100, 125 and 150 mg/ml compared to the negative control group. The pH of S. mutans cultures in the presence of ethanol extract of Soursop leaf at various concentrations was higher than negative control, but there were no differences in pH value between the various concentrations of ethanol extract of Soursop leaf. The extract clearly inhibited S. mutans adhesion to saliva coated hydroxyapatite beads at the concentration  50, 75, 100, 125 and 150 mg/ml compared to the negative control group. Adhesion decreased with increasing concentrations of ethanol extract of Soursop leaf, but there was not significant difference in colony count between the various concentrations of ethanol extract of Soursop leaf. Conclusions: The ethanol extract of Annona muricata leaf can inhibit acid production and adhesion of S. mutans.